2017
DOI: 10.1055/s-0037-1608676
|View full text |Cite
|
Sign up to set email alerts
|

Severe Trampoline Injuries: Incidence and Risk Factors in Children and Adolescents

Abstract: Most severe injuries happened in unsuccessful flips. Children should have an adult supervisor and flips should not be attempted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Greater trauma-energy may result more frequently in proximal humerus fractures than distal humerus or forearm fractures, which are usually caused by falling against the fully extended arm. From an epidemiological point of view, the number of backyard trampolines in the study area has increased since the beginning of 2000s [30, 31]; therefore, it is reasonable that trampoline related distal humerus injuries have increased [32]. However, any increase in horse riding or winter sports within the child population has not been reported in the area, to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Greater trauma-energy may result more frequently in proximal humerus fractures than distal humerus or forearm fractures, which are usually caused by falling against the fully extended arm. From an epidemiological point of view, the number of backyard trampolines in the study area has increased since the beginning of 2000s [30, 31]; therefore, it is reasonable that trampoline related distal humerus injuries have increased [32]. However, any increase in horse riding or winter sports within the child population has not been reported in the area, to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, only fractures were considered, but trampolines are also associated with notable orthopaedic soft-tissue injuries 21 as well as nonorthopaedic injuries, including dental injury, vascular injury, and concussions. 21 , 33 34 35 36 These dimensions were beyond the scope of our study but should be taken into account when considering public health messaging around trampolines.…”
Section: Discussionmentioning
confidence: 99%
“…In one study in the United States, more than one million people visited hospital emergency departments (EDs) due to trampoline-related injuries over a 7-year period, and 288,876 (29.0%) of these injuries were identified as fractures [ 4 ]. A study from Finland showed that the annual incidence of severe trampoline injuries, such as cervical spine injury, in the pediatric population was 6.28 per 100,000 [ 5 ]. Based on these findings, recommendations and regulatory policies to prevent trampoline-related injuries are being made continuously [ 5 - 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study from Finland showed that the annual incidence of severe trampoline injuries, such as cervical spine injury, in the pediatric population was 6.28 per 100,000 [ 5 ]. Based on these findings, recommendations and regulatory policies to prevent trampoline-related injuries are being made continuously [ 5 - 7 ].…”
Section: Introductionmentioning
confidence: 99%